Comparison of the Effectiveness of Long Acting Beta 2 Agonist and Long Acting Antimuscuranics with Long Acting Beta 2 Agonist/Long Acting Antimuscuranics Plus Inhaled Corticosteroids in preventing Exacerbations of patients with Chronic Obstructive Pulmona - Aqeela Naeem, Asma Sabir, Kanwal Fatima Khalil, Asma Ambreen, Shumiala Awan, Jamila Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the efficacy of long acting beta 2 agonist and long acting antimuscuranics with long acting beta 2 agonist/long acting antimuscuranics plus inhaled corticosteroids in preventing exacerbations of chronic obstructive pulmonary disease and its relationship with increased eosinophils level. Study Design: Randomized control trial Place and Duration Study: Department of Pulmonology, Fauji Foundation Hospital, Rawalpindi from 7th February 2018 to 6th August 2018. Methodology: Seventy patients with chronic obstructive pulmonary disease were enrolled. They were divided in two groups; Group A receiving LABA/LAMA combination and Group B receiving LABA/LAMA plus ICS combination. Both groups treatment efficacy was related with increased eosinophils count. Patients were regularly followed and number of exacerbations in the first three months was noted. At the completion of the study, the rate of exacerbations among the 2 groups was compared. Results: The rate of efficacy in LABA/LAMA and LABA/LAMA plus ICS group was 62.9% and 85.7% respectively. Efficacy was more achieved in LABA/LAMA plus ICS group in patients whose eosinophil count was ≥ 2% up to 90.5% and was 78.6% whose eosinophil count was ≤ 2%. Conclusion: Treatment with long acting beta 2 agonist/long acting antimuscuranic plus inhaled corticosteroids is more effective in preventing exacerbations of patients with advanced COPD than with long acting beta 2 agonist and long acting antimuscuranic. Keywords: Chronic obstructive pulmonary disease, Long acting beta 2 agonist, Long acting antimuscuranics, Inhaled corticosteroids, Efficacy, Eosinophilia